Assessing Workplace Relational Civility (WRC) with a New Multidimensional “Mirror” Measure - Di Fabio, Annamaria; Gori, Alessio (Frontiers in Psychology, 2016)
This article first introduces a new psychological construct and then presents the psychometric properties of a new multidimensional measure for assessing workplace relational civility (WRC). This new self-report mirror measure has two specular sections (Part A – Me with others; Part B –Others with me) that can assess individuals’ relational patterns regarding civility and that can help reduce the bias in the assessment process. The results of exploratory factor analysis revealed a factor structure with three robust dimensions (relational decency, relational culture, and relational readiness) exhibiting good values of internal consistency. Confirmatory factor analysis showed, in turn, a good fit of the model to the data. The correlations between the sections of the measure and the 11 instruments used were significant and in the expected directions. These results suggest that this new, brief mirror measure for assessing WRC can be easily employed in different organizational contexts to open different typologies of actions on the basis of the three dimensions, thereby facilitating the construction of a safer and more decent relational work environment.